2003
DOI: 10.1002/ejsp.184
|View full text |Cite
|
Sign up to set email alerts
|

Testing an attribution‐of‐blame model of judgments of injustice

Abstract: The attribution-of-blame model of judgments of injustice, which is the focus of this article, depicts judgments of injustice as blaming of an actor who is seen as responsible for the violation of the entitlement of somebody else without sufficient justification. Responsibility and blame are conceptualized in the model in accordance with Heider (1958) and Shaver (1985). The article briefly describes the background and the propositions of the model and its scope. Then it reports a series of four correlational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 38 publications
(33 reference statements)
3
67
0
6
Order By: Relevance
“…As Mikula (2003) argues, an injustice is likely to be perceived when an offender is considered responsible for the violation of another's entitlement that cannot be justified through other, higher-order ethical motives. Most, if not all, justice theories assume that experiences of injustice generally elicit the motivation to restore justice (e.g.…”
Section: Retributive and Restorative Justicementioning
confidence: 99%
“…As Mikula (2003) argues, an injustice is likely to be perceived when an offender is considered responsible for the violation of another's entitlement that cannot be justified through other, higher-order ethical motives. Most, if not all, justice theories assume that experiences of injustice generally elicit the motivation to restore justice (e.g.…”
Section: Retributive and Restorative Justicementioning
confidence: 99%
“…For example, in organizational settings it is easy to find examples of the importance of understanding how people deal with being overpaid (e.g., Adams, 1965;Adams & Freedman, 1976;Greenberg, 1982). Furthermore, research on intimate relationships has revealed that being better off than your partner can play an important role in how people react to issues in their intimate relationships (e.g., Mikula 2003;Van Yperen & Buunk, 1990).…”
mentioning
confidence: 99%
“…For example, in the 1960s, Jacques (1961) and Adams (1965) started the inquiry into this fascinating topic, and since then many researchers have further studied this frequently occurring instance of injustice. Researchers have shown that overpaid people try to restore equity (Adams, 1965;Walster et al, 1973Walster et al, , 1978, tend to feel only moderately satisfied with their outcome (Adams, 1965;Buunk & Van Yperen, 1991;Van Yperen & Buunk, 1990;Walster et al, 1973;Walster et al, 1978), and try to justify their advantage, for example, by adjusting the types of comparisons that they make (Austin, 1977;Mikula, 2003).…”
mentioning
confidence: 99%
“…For instance, they may believe the tax authority tolerates tax avoidance schemes of the wealthy, but intervenes when the same schemes are adopted by ordinary taxpayers (Hobson, 2002;Murphy, 2003). In line with Mikula's (1993Mikula's ( , 2003 attribution of blame model, we would expect that taxpayers' explanations of the tax authority's actions determine how much responsibility and blame they attribute to the authority, and how much injustice and resentment they feel.…”
Section: Discussionmentioning
confidence: 96%